Selective Anodic Oxidation of Solketal as Acetal‐Protected Glycerol over Nickel Boride in Alkaline Media to Glyceric Acid. Issue 4 (9th December 2021) - Cychy, Steffen; Lechler, Sebastian; Muhler, Martin
Abstract: Alkaline anodic oxidation of glycerol suffers from facile C−C bond cleavage, especially when using non‐precious metal electrocatalysts, which limits the yield of more valuable C3 oxygenates. Usually, a high C3 selectivity is a tradeoff with conversion for most catalysts. Thus, we used solketal as the reactant, which is acetal‐protected glycerol with acetone. CV experiments showed that solketal is oxidized over nickel boride (Nix B) at potentials where NiOOH is formed. Electrolysis over Nix B in a thin‐film spectroelectrochemical flow cell at 1.58 V vs. RHE to avoid pronounced oxygen evolution showed a stable current density of ca. 6 mA cm −2 . Simultaneously recorded ATR‐FTIR spectra revealed solketal conversion to solketalate and formate. Indeed, 59 % conversion and 77 % selectivity to glyceric acid were determined by HPLC after acidic cleavage of the acetal, resulting in a yield of 45 %. Therefore, solketal is a promising reactant for the selective electrosynthesis of glyceric acid. Abstract : Protected alternative : Solketal is applied as a promising alternative to glycerol to increase the glyceric acid yield in alkaline anodic oxidation. By protecting vicinal hydroxyl groups as an acetal, the strong tendency of non‐noble catalysts to split C−C bonds is decreased. The reaction, monitored by ATR‐IR spectroscopy, produces solketalate in a thin‐film flow cell. Glyceric acid is obtained after acidification with 79 % selectivity and 45 % yield determined by HPLC.